Jasmonate‐dependent modifications of the pectin matrix during potato development function as a defense mechanism targeted by Dickeya dadantii virulence factors. (16th January 2014) - Taurino, Marco; Abelenda, Jose A.; Río‐Alvarez, Isabel; Navarro, Cristina; Vicedo, Begonya; Farmaki, Theodora; Jiménez, Pedro; García‐Agustín, Pilar; López‐Solanilla, Emilia; Prat, Salomé; Rojo, Enrique; Sánchez‐Serrano, José J.; et al.
Summary The plant cell wall constitutes an essential protection barrier against pathogen attack. In addition, cell‐wall disruption leads to accumulation of jasmonates (JAs), which are key signaling molecules for activation of plant inducible defense responses. However, whether JAs in return modulate the cell‐wall composition to reinforce this defensive barrier remains unknown. The enzyme 13–allene oxide synthase (13–AOS) catalyzes the first committed step towards biosynthesis of JAs. In potato (Solanum tuberosum), there are two putative St13–AOS genes, which we show here to be differentially induced upon wounding. We also determine that both genes complement an Arabidopsis aos null mutant, indicating that they encode functional 13–AOS enzymes. Indeed, transgenic potato plants lacking both St13–AOS genes (CoAOS1/2 lines) exhibited a significant reduction of JAs, a concomitant decrease in wound‐responsive gene activation, and an increased severity of soft rot disease symptoms caused by Dickeya dadantii. Intriguingly, a hypovirulent D. dadantii pel strain lacking the five major pectate lyases, which causes limited tissue maceration on wild‐type plants, regained infectivity in CoAOS1/2 plants. In line with this, we found differences in pectin methyl esterase activity and cell‐wall pectin composition between wild‐type and CoAOS1/2 plants. Importantly, wild‐type plants had pectins with a lower degree of methyl esterification, which are the substrates of the pectate lyases mutated in the pel strain. These results suggest that, during development of potato plants, JAs mediate modification of the pectin matrix to form a defensive barrier that is counteracted by pectinolytic virulence factors from D. dadantii.